Інтернаціоналізація та глобалізація як ключові чинники міжнародного співробітництва в сфері вищої освіти - Чабала, О. (НТУ "ХПІ", 2015)
В статті увага зосереджена на процесах інтернаціоналізації та глобалізації освіти та їх взаємозв’язку. В науковій розвідці зроблено висновок про те, що в освітній галузі інтернаціоналізація є чинником інтеграції ВНЗ, а глобалізація, з одного боку сприяє конкуренції в освітній сфері, а з іншого - вимагає постійного розвитку і вдосконалення освіти зорієнтованої не тільки на національний, але й міжнародний рівні. Відповідні процеси впливають на освітні інституції та системи, сприяючи руху до нових форм та якостей на освітньому, інституціональному та глобальному рівнях.

The article focused on processesof internationalization and globalization of education and their interrelation. In scientific research author has drawn a conclusion that the internationalization of education is a factor of integration of higher educational institutions, but globalization promotes the educational competition and demands continuous development and improvement of education which focused not only on national, but also international levels. These processes influenced educational institutions and systems, promoting transition to new forms and qualities at educational, institutional and global levels.
Internationalization and globalization as a factor of international cooperation in the high education systems
Keywords: освітня галузь; інтеграція ВНЗ; конкуренція; вдосконалення освіти; internationalization; globalization; education